Training basic echocardiography to pediatric residents: need of the hour - Prasad, Arun; Kumar, Pradeep; Yankappa, N. (International Journal of Contemporary Pediatrics, 2021)
Most of the cardiac abnormalities which pediatricians come across, require echocardiography for confirming the diagnosis. Due to the introduction of 'point of care ultrasonography' and widespread availability of ultrasonography equipment in clinical care areas, pediatricians are able to diagnose some of these cardiac abnormalities; however, they are unable to make a prompt echocardiographic diagnosis by themselves in most of these cardiac conditions due to lack of echocardiography skills. Pediatric residents and consultants, especially those who are involved in providing care in pediatric emergency, pediatric ICU, and neonatal ICU, should learn the skills of basic echocardiography for making the quicker diagnosis of such conditions and improving patient care. Subcostal view echocardiography can detect many cardiac abnormalities through a single echocardiographic window. There is a need of formulating a need-based basic Echocardiography training program to be incorporated into the Pediatric residency curriculum.